1993
DOI: 10.1136/bmj.307.6917.1467
|View full text |Cite
|
Sign up to set email alerts
|

Understanding variation in rates of referral among general practitioners: are inappropriate referrals important and would guidelines help to reduce rates?

Abstract: Objectives-To determine the extent to which variation in rates of referral among general practitioners may be explained by inappropriate referrals and to estimate the effect of implementing referral guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 10 publications
2
49
1
3
Order By: Relevance
“…These included more training in specific procedures, consultation with a trusted colleague, telephone consults with a specialist, the presence of a health educator, availability of clinical practice guidelines, longer visit lengths, computerized medical expert systems, MEDLINE search capabilities, and subspecialty texts (Donohoe et al, 1999) Although these studies suggest that physicians who make inappropriate referrals may require additional training or support to reduce this behavior, not all researchers agree. Fertig et al (1993) found that a high variation in referral rates among PCMs was not explained by inappropriate referrals. They concluded that the application of referral guidelines could help improve the quality of referrals but probably would not be useful in reducing the number of referrals to hospitals.…”
Section: Referral Process Improvement 18mentioning
confidence: 96%
“…These included more training in specific procedures, consultation with a trusted colleague, telephone consults with a specialist, the presence of a health educator, availability of clinical practice guidelines, longer visit lengths, computerized medical expert systems, MEDLINE search capabilities, and subspecialty texts (Donohoe et al, 1999) Although these studies suggest that physicians who make inappropriate referrals may require additional training or support to reduce this behavior, not all researchers agree. Fertig et al (1993) found that a high variation in referral rates among PCMs was not explained by inappropriate referrals. They concluded that the application of referral guidelines could help improve the quality of referrals but probably would not be useful in reducing the number of referrals to hospitals.…”
Section: Referral Process Improvement 18mentioning
confidence: 96%
“…13 A larger question than whether UR decreases referral rates, however, is whether it leads to more cost-effective care. There is little agreement on when patients should be referred from primary to specialty care, 8 and there is evidence for both underutilization 3,14 and overutilization 3,6,7 of specialty services. The enormous variation in physician referral rates is problematic, and UR may be one mechanism to reduce the variation.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Referral rates vary even when there are no associated financial consequences, [1][2][3] and the variation cannot be explained by patient factors or practice characteristics. 1 Thus, physicians may have individual referral thresholds, 4 and some patients may be referred unnecessarily.…”
mentioning
confidence: 99%
“…That part of variation that is not legitimate should be reduced. Although, up to now, there is no evidence that less variation is related to a higher quality of care (Weide et al 1999;Fertig et al 1993). Patients should receive the treatment that works best, against acceptable costs.…”
Section: Conclusion and Discussionmentioning
confidence: 99%